A Glimpse of the World of Volatile Fatty Acids Production and Application: A review. Issue 1 (1st January 2022) - Agnihotri, Swarnima; Yin, Dong-Min; Mahboubi, Amir; Sapmaz, Tugba; Varjani, Sunita; Qiao, Wei; Koseoglu-Imer, Derya Y.; Taherzadeh, Mohammad J.
ABSTRACT: Sustainable provision of chemicals and materials is undoubtedly a defining factor in guaranteeing economic, environmental, and social stability of future societies. Among the most sought-after chemical building blocks are volatile fatty acids (VFAs). VFAs such as acetic, propionic, and butyric acids have numerous industrial applications supporting from food and pharmaceuticals industries to wastewater treatment. The fact that VFAs can be produced synthetically from petrochemical derivatives and also through biological routes, for example, anaerobic digestion of organic mixed waste highlights their provision flexibility and sustainability. In this regard, this review presents a detailed overview of the applications associated with petrochemically and biologically generated VFAs, individually or in mixture, in industrial and laboratory scale, conventional and novel applications. Graphical Abstract: uf0001